STUDY OF FINAL-STATE PHOTONS IN HADRONIC Z0 DECAY AND LIMITS ON NEW PHENOMENA - Abreu, P; Adam, W; Adami, F; Adye, T; Akesson, T; Alekseev, G; Allen, P; Almehed, S; Alvsvaag, S; Amaldi, U; Anassontzis, E; Antilogus, P; et al. (1992)
The differential cross section for final state radiation from primary quarks is obtained from a study of isolated energetic photons produced in the reaction e+e-→Z0→hadrons+γ, as measured in the DELPHI detector at the CERN LEP collider. When combined with the measurement of the total hadronic width of the Z0, the observed rate determines the electroweak coupling constants of up and down type quarks, i.e., Mathematical expression No evidence is seen for additional photon production from anomalous decays of the Z0 or from decays of new particles. This measurement leads to upper limits on the production cross section times branching fraction of (a) the Higgs boson in the reaction e+e-→Z0→H +γ, H→hadrons, (b) an excited quark, q*→q+γ, and (c) the contribution of an anomalous decay of the Z0 into a photon and hadrons. These limits, all at the 95% confidence level, vary from 3 to 10pb as the mass of the intermediate state (H, q* or Z*) varies from 10 GeV/c2 to 80 GeV/c2. © 1992 Springer-Verlag.